Analysis of a radial flux-air-cored permanent magnet machine with a double-sided rotor and non overlapping windings - Randewijk, Peter-Jan (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.